Medicinal Importance Of Rumex Acetosa - Rana Mohsin ali; Shafqat Zaidi; Syaifuddin Amir; Ayu Indayanti Ismail; Aulia Rahmadhani (International Journal of Technology and Education Research, 2023)
Rumex acetosa, also known as sorrel, is a perennial herbaceous plant belonging to the buckwheat family. Both as a cultivated plant and as a wild species, sorrel has been used for thousands of years. Numerous bioactive substances have been discovered in recent studies that have examined Rumex's various phytochemical and pharmacological capabilities. Plants have several health benefits because of the abundance of phytochemicals found in plants, including phenylpropanoids, isoprenoids, alkaloids, sulfated compounds, peptides, and polysaccharides, they possess biological qualities including anticancer, antifungal, anti-dysenteric, antioxidant, anti-inflammatory, antiulcer, antibacterial, anti-coagulant, and antihypertensive properties. Sorrel provides a decent source of micro-and macro-nutrients in its leaves. So when we use uncooked plant components, excessive quantities of oxalic acid impair the bioavailability of some nutrients, particularly calcium. Because of their antioxidant and anti-microbial properties, Rumex species are used to preserve food. Food plants are taken into account not only both from a nutritional aspect but as a preventative measure for the most prevalent lifestyle diseases, like diabetes, cardiovascular illnesses, and cancer. To demonstrate the full impact of so many sorrel chemicals, more research is required. More research needs to be done on phytochemistry's potential as a medicine. More study is required to support these medical claims; nonetheless, this review attempts to bridge the knowledge gap and so provides sufficient data for ongoing studies on its potential as a functional food.